Marketing Strategy Universitas Singaperbangsa Karawang - Fajar Ramadhan; Syamsu Yusuf (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2020)
Higher education in Indonesia is a national education subsystem that includes undergraduate, master's, specialist, doctoral, and diploma programs. Higher education institutions are obliged to organize education, research, and community service in accordance with their vision, mission, goals, tasks, and authority. A large number of universities has led to intense competition in getting prospective students. Therefore, universities must have a good "marketing strategy" to continue to exist in the face of competition between universities. Marketing strategies must be based on marketing objectives that consider environmental aspects (Dharmmesta, 2014). Marketing strategies took in connection with existing conditions, SWOT analysis, organization, and control at the University of Singapore Karawang based on Education Quality Standards (accredited). Efforts to monitor the implementation of marketing strategies related to the achievement of performance targets for increasing the number of applicants, including re-registration, the achievement of external and internal marketing activities.